Public sector enterprises in India: Enhancing geo-strategic reach and exports - Arpita Mukherjee; Angana Parashar Sarma; Ankita Barah; Arush Mohan (Indian Council for Research on International Economic Relations (ICRIER), 2020)
Public sector enterprises (PSEs) have been one of the key drivers of economic development in several countries, including India. While many countries have gradually moved away from the PSE model of growth, in the year 2019, around 25 percent of the Fortune Global 500 companies were PSEs. As countries use PSEs to enhance their geo-strategic reach, it has raised concerns about the potential influence of governments on these enterprises in destination markets and the emergence of an uneven playing field between PSEs and the private players. Therefore, the role of PSEs is being increasingly discussed in international forums such as the WTO and G20 and trade rules on PSEs are being negotiated in several bilateral/regional trade agreements. India is among the top eight countries in the world with a large number of PSEs that play a key role in meeting the country's geo-strategic interests and export targets. At the same time, several PSEs are loss-making units and are plagued by operational inefficiencies. In this context, this paper examines the role of Indian PSEs in expanding the country's geo-strategic reach and exports. It analyses the experiences of PSEs in select countries and presents the discussions and debates on PSEs in different international forums. Based on in-depth meetings with stakeholders, it identifies the challenges faced by the Indian PSEs and provides policy recommendations on how to prioritise and address them.
Keywords: E61; F13; G38; L32; P45; 330; PSEs; state-owned enterprises; geo-strategy; exports; India; policy; WTO; G20